Effect of Ph on the Growth and Survival of Juvenile Common Carp (Cyprinus Carpio L.) - Nasir, Noori AbdulNabi; Yesser, AbdulKareem Taher; Al-Hamadany, Qusay Hamid (Iraqi Journal of Science, 2019)
Common carp ( Cyprinus carpio L.) juveniles averaging 7.68± 0.25 - 8.12± 1.14 g in weight were used for 6 weeks to investigate their survival and growth preferences. The experimented carp were stocked at 12 tanks formerly adjusted with different pH levels values as: 6.0, 7.0, 8.0 and 9.0. Growth and survival of common carp was assessed every Sunday of each week. Growth rates significantly (P < 0.05 ) increased at pH 7 and pH8 respectively. Therefore, the results suggest that the water with pH ranged from 7 to 8 was the best range for growth performance and survival rate of carp. Feed conversion ratio (FCR) improved at pH 6 and 9 respectively. In general, the results indicated that water pH 7- 8 could be more appropriate to juvenile carp culture for best growth performance and survival rate.